'The Indian Maharaja under check…': The Abolition of Privy Purses and Princely Privileges, 1967–71 and the End of an Era. Issue 2 (September 2022) - Ankit, Rakesh
Abstract : This article attends to the abolition of the privy purses and princely privileges of ex-rulers achieved between May 1967 to December 1971 in a controversial constitutional episode, in a period of transition for Indian democracy. Moving beyond the usual figures under focus, namely Prime Minister Indira Gandhi and her Principal Secretary P.N. Haksar, it brings to fore a wider cast of characters and their concerns during this campaign. Second, it seeks to take the established binary between the old of the Indian National Congress and the new of Indira's Congress (Ruling) following the split in 1969, to stand for a wider generational passage of time at both international and internal levels. Third, probing this overlapping interaction, it presents it as one among final episodes of independent India emerging from its British world of 1947, whose relevance can be sketched beyond pressure politics inside a party and mass politics outside it. Finally, it presents this episode as a prism through which one can see the end of the 'first phase' of India's democracy and one of its inherited institutions.